Deutsche Köhler-Fischerei im Nordost-Atlantik 1976 - Reinsch, H.H. (1977)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010